Incidental finding of type A aortic dissection in a paediatric heart transplant recipient. (September 2019) - D'Addese, Laura; Komarlu, Rukmini; Zahka, Kenneth
Abstract: Aortic dissection causes significant morbidity and mortality in adults and treatment guidelines are based on well-documented risk factors. Conversely, dissection after orthotopic heart transplantation is very rare, especially in the absence of infection, hypertension, or donor–recipient aortic size mismatch. Several forms of CHD are associated with aortic dilatation, but the incidence of aortic dissection and aneurysm in children is also low, which makes use of adult guidelines in children challenging. We present a 17-year-old Amish female with a homozygous gene mutation in the MYBPC3 gene known to cause lethal, infantile hypertrophic cardiomyopathy. She underwent orthotopic heart transplantation and then developed an asymptomatic aortic dissection despite no known risk factors.